PROFESSIONAL-ORIENTED ACTIVITIES OF THE FUTURE PRIMARY SCHOOL TEACHER IN THE CONDITIONS OF INFORMATIZATION AND COMPUTERIZATION OF EDUCATION - Kotkova, V.V. (Pedagogy of Higher and Secondary Education, 2010)
In the article are described the ways of informative-communicative technologies in professional-directed preparation of future primary school teachers as a tendency of devel opment the educatoin in the conditions of informatization and computerization.